Evaluation of the 2018-2023 Bojonegoro Regent's Priority Program at the Manpower Service in creating 100,000 New Jobs - Agnecia, Zinta; Wulandari, Septi; Rupiarsieh, Rupiarsieh (Riwayat: Educational Journal of History and Humanities, 2025)
This research aims to evaluate the implementation of the 2018-2023 Bojonegoro Regent's priority program, which focuses on creating 100,000 new jobs to overcome the high unemployment rate in Bojonegoro Regency and using descriptive research methods with a qualitative approach to get an in-depth picture of program implementation. Evaluation indicators are used based on the CIPP model (context, input, process, product). Primary data was obtained from structural interviews with labor service officials, job seekers, and the Bojonegoro Regency DPRD commission, secondary data from public documentation studies, and data from the research location.The research results show that this program includes skills training based on local potential and community interest surveys to increase the effectiveness of implementation. This program succeeded in exceeding the target by creating more than 119,892 jobs. However, several obstacles were found, such as budget limitations, the impact of the COVID-19 pandemic, and the need for an adequate monitoring system. This program positively impacts poverty reduction and empowers the community's economy. If necessary, closer collaboration with the industrial sector, the development of digital reporting technology, and more effective budget planning are needed. Future research is recommended to develop an integrated monitoring system and explore the further impact of external factors.